Catheter Ablation A Current Approach on Cardiac Arrhythmias (Springer Singapore, 2018)
This book provides cutting-edge theories and techniques for catheter ablation of all kinds of tachyarrhythmias. Catheter ablation has been a main therapeutic method for tachyarrhythmias for more than thirty years now, and countless operations have been successfully performed. It is crucial for electrophysiologists to diagnose arrhythmia mechanisms correctly and to optimize ablation methods, especially in Japan, one of the world's fastest-aging countries and where many of this book's authors are based. The volume is divided into eight parts. The first three parts present the basic theories and novel insights essential to diagnosing and performing catheter ablations. In turn, the latter five parts highlight practical ablation methods in the context of frequently encountered arrhythmias cases, as well as rare ones such as chanellopathies. Written for electrophysiologists who treat patients with cardiac arrhythmias, the book offers reader s essential tips and tricks for the optimal treatment of arrhythmias.